Bioactive compounds and physical and chemical characteristics of mini tomatoes: influence of postharvest treatments - Schwarz, Kélin (2016)
Tomatoes are among the most cultivated and used vegetables in the world. They are very succeptible to post harvest losses due to high perishability, therefore the use of postharvest treatments may contribute to conservation of this fruit, however the treatments might affect significantly physico-chemical, sensory and nutritional characteristics of tomatoes. Given the perishability of tomato and the economic importance of small tomato fruits, the purpose of the present study was to determine the effect of gamma radiation, carnauba coating and 1-MCP treatments on tomato fruit quality during storage. The study may be divided into two parts. In the first, mini tomatoes cv. Sweet Grape were harvested at breaker stage, divided into 4 grous and treated with gamma radiation (0.6 kGy), carnauba coating (1 L 1000 kg-1) and 1-MCP (500 nL L-1) and then stored at 25±2°C for 30 days with a control group of tomatoes. In the seconnd part, tomatoes harvested at light-red stage were submitted to the same treatments and storage period. Every 6 days tomatoes were evaluated for color modifications, fruit firmness, souble and total pectin (only for light-red tomatoes), mass loss, titratable acidity (TA), soluble solids (SS), SS/TA ratio, carotenoids profile, formation of lycopene isomers, total phenolic compounds, ascorbic acid and antioxidant capacity. For tomatoes harvested at breaker stage and submitted to the treatments the results showed mass loss was delaying mainly by carnauba wax, and to a lesser extend by 1-MCP. Fruit firmness were better retained for 1-MCP treated fruits and carnauba treatment showed a transient effect in preserving fruit firmness. SS/TA of tomatoes treated with gamma radiation and carnauba presented no differences from control values, and were lower with the application of 1-MCP. Color was negatively affected by 1-MCP and earlier changed (6th day) when gamma radiation was applied. In relation to bioactive compounds of tomatoes harvest at breaker stage, results indicated gamma radiation and 1-MCP decreased the final content of lycopene and produced more (Z)-isomers of lycopene. Gamma radiation also induced a decreased in ?-carotene and an increased in phenolic compounds by the end of storage period. 1-MCP treatment promoted a slow down increase in ascorbic acid content during storage. Antioxidant capacity of the hydrophilic fraction was not dramatically affected by treatments and the lipophilic fraction was lower, especially for 1-MCP fruits. In addition, contents of ?-carotene, lycopene, (Z)-isomers of lycopene, ascorbic acid and antioxidant capacity increased during the period of storage while contents of lutein and phenolic compounds tended to decrease. Regarding tomatoes harvest at light-red stage, the most effective treatments for delaying fruit firmness and mass loss was carnauba and 1-MCP, while gamma radiation was the treatment with higher mass loss and the less fruit firmness, which could be associated with the higher solubilization of pectins promoted by radiation treatment. Color (L* and Hue) was mainly affected by 1-MCP treatment which delayed color development, however, by the end of storage, the values were not different from the other treatments. SS/TA ratio was lower for fruits treated with 1-MCP and TA was not so dramatically affected by treatments. Furthermore, mini tomatoes harvested at light-red stage, demonstrated irradiation induced changes in the final content of lycopene, increasing it, and formed less (13Z)-lycopene, while 1-MCP and carnauba coating slow down the increase in lycopene and slown down the decrease of ascorbic acid and phenolic compounds. Antioxidant capacity of lipophilic fraction was not affected by treatments and the hydrophilic fraction was lower for irradiated fruits only on day 0 as well as phenolic compounds. In the other days, no differences among treatments were observed for hydrophilic antioxidant capacity. Considering the results, the best combination of SS and TA and fruit preservation for mini tomatoes harvest at breaker stage was promoted by carnauba coating, which seems to be the treatment that causes fewer changes in bioactive compounds of breaker tomatoes. However, when mini tomatoes were harvested at light-red stage, SS/TA ratio and color were better and, to preserve the quality of these fruits, besides carnauba coating, 1-MCP also could be indicated